Development of Young Entrepreneurs in the Competitive Era: A Systematic Literature Review - Kartono, Kartono; Suyatin, Suyatin; Murtiyoko, Heri (Universitas Negeri Makassar, 2025)
The purpose of this study is to understand the Development of Young Entrepreneurs in the Competitive Era and the Strategies for Developing Young Entrepreneurs in the Competitive Era through a Systematic Literature Review. This research uses an exploratory descriptive approach with a focus on literature review or bibliographic studies, referring to various literatures such as books, dissertations, scientific journals, and the internet. The results of the study can be concluded that the development of young entrepreneurs in the competitive era involves various aspects such as entrepreneurship education, access to technology, capital, and government policies. With appropriate support from various parties, the younger generation has great potential to become successful young entrepreneurs. The strategies for developing young entrepreneurs are carried out in several aspects, including: Motivation Aspect, Creativity Aspect. Creativity is an important source in creating competitive advantages for all organizations in terms of growth and change, followed by Leadership Aspect, Marketing Aspect, and Business Legality Aspect. Therefore, these aspects need to be considered to achieve successful young entrepreneurs.